Transduction of Systemically Administered Adeno-Associated Virus in the Colonic Enteric Nervous System and c-Kit Cells of Adult Mice - Wang, Lixin; Yuan, Pu-Qing; Challis, Collin; Ravindra Kumar, Sripriya; Taché, Yvette (Frontiers in Neuroanatomy, 2022)
Systemic delivery of adeno-associated virus (AAV) vectors transduces the enteric nervous system. However, less is known on the mapping and morphological and neurochemical characterization in the adult mouse colon. We used AAV9-CAG-GFP (AAV9) and AAV-PHP.S-hSyn1-tdTomato farnesylated (PHP.S-tdTf) to investigate the segmental distribution, morphologies and neurochemical coding of the transduction. The vectors were retro-orbitally injected in male and female adult mice, and 3 weeks later, the colon was prepared for microcopy with or without immunohistochemistry for neuronal and non-neuronal markers. In contrast to the distributions in neonatal and juvenile rodents, the AAV transduction in neurons and/or nerve fibers was the highest in the proximal colon, decreased gradually in the transverse, and was sparse in the distal colon without difference between sexes. In the proximal colon, the AAV9-transduced myenteric neurons were unevenly distributed. The majority of enteric neurons did not have AAV9 expression in their processes, except those with big soma with or without variously shaped dendrites, and a long axon. Immunolabeling demonstrated that about 31% neurons were transduced by AAV9, and the transduction was in 50, 28, and 31% of cholinergic, nitrergic, and calbindin-positive myenteric neurons, respectively. The nerve fiber markers, calcitonin gene-related peptide alpha, tyrosine hydroxylase or vasoactive intestinal polypeptide co-localized with AAV9 or PHP.S-tdTf in the mucosa, and rarely in the myenteric plexus. Unexpectedly, AAV9 expression appeared also in a few c-Kit immunoreactive cells among the heavily populated interstitial cells of Cajal (ICC). In the distal colon, the AAV transduction appeared in a few nerve fibers mostly the interganglionic strands. Other types of AAV9 and AAV-PHP vectors induced a similar colonic segmental difference which is not colon specific since neurons were transduced in the small intestine and gastric antrum, while little in the gastric corpus and none in the lower esophagus. Conclusion These findings demonstrate that in adult mice colon that there is a rostro-caudal decrease in the transduction of systemic delivery of AAV9 and its variants independent of sex. The characterization of AAV transduction in the proximal colon in cholinergic and nitrergic myenteric neurons along with a few ICC suggests implications in circuitries regulating motility.